Guideline for managing acute diarrhea in the context of pharmaceutical care - Barbosa, Laís de Fátima; Moreira Cotrim, Francisca; Alves Moreira Marques, Luciene; Laismann, Nara Amanda; Fonseca Lima, Rodrigo; Barbosa Antunes, Rafaela; de Albuquerque Vaz, Juliana Maria; Santos Santana, Rafael; Marques dos Reis, Tiago (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2026)
Objective: To systematize, through evidence-based practice, the management of self-limited cases of acute diarrhea in the context of Pharmaceutical Care. Methods: To prepare the guideline, the ADAPTE method was adopted as a structured process of literature review and document construction. The AGREE II and GRADE tools were also used to analyze the practice guides selected during the process and to categorize the evidence, respectively. Results: After preparation, it was observed that the pharmaceutical anamnesis is an important step for confirming the self-limiting nature of acute diarrhea, preventing acute viral gastroenteritis, and referring in cases where warning signs such as severe dehydration or associated symptoms are suspected. Non-pharmacological measures generally showed strong degrees of recommendation. Oral rehydration therapy and continued breastfeeding in infants show high levels of evidence. Regarding pharmacological measures, as an adjunct to rehydration therapy, there is first-line treatment, which includes over-the-counter medications, and second-line treatment, which consists of antidiarrheals, antisecretory agents, antibiotics, and antiparasitic drugs. Conclusion: Pharmaceutical anamnesis proved to be fundamental. The pharmacist's role is relevant in improving clinical management, promoting rational drug use, and facilitating timely referral of patients with signs of greater severity.